The circular economy strategies based on household waste management: Promoting environmental quality with the system dynamics approach - Kristianto, Aloysius Hari; Yuliana, Yuliana; Suratman, Eddy; Yani, Akhmad; Restiatun, Restiatun (Publisher of Widyagama University of Malang (UWG Press), 2024)
The circular economy is an innovative economic model that converts waste into valuable products, while offering substantial benefits for both regional and national economies. This study investigated how the household waste management practices affected environmental degradation and public health using the System Dynamics technique. The study drew on various sources, including mass media, expert opinions, time series data, and scientific publications, to assess the effect of waste on water, air, and public health quality. The findings indicated a link between population growth and the increased waste generation, particularly from the domestic sources. The unmanaged waste poses a threat to air and water quality, while highlighting the need for an improved waste management. A 3R approach (Reduce, Reuse, and Recycle) in the circular economy offers clear environmental and economic benefits, such as the reduced environmental impact, the increased income generation, and the enhanced investment and job creation. Additionally, the circular economy promotes the recycling and green entrepreneurship, while boosting investment and job creation. Collaboration between governments and business owners strengthens local distribution and marketing, enhancing local self-sufficiency. In summary, the adoption of a circular economic model offers substantial and wide-ranging benefits for economies at both the regional and national levels. JEL Classification: K32; O44; Q50